'Equal pay now! Into the political arena', 1951 (1951)
1951 1945-1960 "'Equal pay now! Into the political arena', 1951" [EP0104], 1951 This leaflet was issued by the Staff Side of the Civil Service National Whitley Council as part of its 1951 equal pay campaign.